Legal Certainty of Using Indonesian Language in Notarial Deeds - Keristion, Keristion; Sesung, Rusdianto (PT. Hafasy Dwi Nawasena, 2025)
Indonesian is the official language of the country used in various aspects of life, including in law and official documents. The use of Indonesian in notarial deeds is important because notarial deeds are legal products that have binding force. This research is entitled “Legal Certainty in the Use of Indonesian in Notarial Deeds”, which aims to examine the extent to which legal certainty is guaranteed in the use of Indonesian in deeds made by notaries. Notaries have an important role in ensuring that the deeds made meet legal requirements, including the use of clear language that does not cause ambiguity. The use of Indonesian language in notarial deeds has been regulated in various laws and regulations. Law No. 24/2009 on the Flag, Language and State Emblem requires the use of Indonesian language in official state documents. Compliance with this provision aims to provide legal protection for the parties involved in the agreement or legal agreement. With this research, it is hoped that it can provide a deeper understanding of how legal certainty can be guaranteed through the use of Indonesian language in notarial deeds and its implications for legal protection for the community.